Cholinergic correlates of cognitive impairment in Parkinson's disease: comparisons with Alzheimer's disease. Issue 5 (May 1985) - Perry, E K; Curtis, M; Dick, D J; Candy, J M; Atack, J R; Bloxham, C A; Blessed, G; Fairbairn, A; Tomlinson, B E; Perry, R H
Abstract : Dementia in Parkinson's disease has previously been attributed to the presence in the cerebral cortex of Alzheimer-type neuropathological abnormalities. New evidence suggests, however, that dementia in this disease usually occurs in the absence of substantial Alzheimer-type changes in the cortex and may be related to abnormalities in the cortical cholinergic system. Thus, in Parkinsonian patients with dementia there were extensive reductions of choline acetyltransferase and less extensive reductions of acetylcholinesterase in all four cortical lobes. Choline acetyltransferase reductions in temporal neocortex correlated with the degree of mental impairment assessed by a test of memory and information but not with the extent of plaque or tangle formation. In Parkinson's but not Alzheimer's disease the decrease in neocortical (particularly temporal) choline acetyltransferase correlated with the number of neurons in the nucleus of Meynert suggesting that primary degeneration of these cholinergic neurons may be related, directly or indirectly, to declining cognitive function in Parkinson's disease.